Travail coopératif avec un robot pédagogique : quels effets sur le ressenti des élèves avec TSA ? - Magalie Duprat (Éducation et Socialisation, 2022)
The reception of pupils with autism spectrum disorders (ASD) to primary school aims not only developing their academic skills, but also to facilitate their participation in social life within the class group and school. The role of the out of class teaching unit (UEE) is precisely to contribute to create this favorable context. In many studies, the use of digital tools has shown its effectiveness at facilitating learning. However, the degree of inclusive operationality of a digital working environment has not yet been evaluated. The experimental project is thus interested in the role that a digital device used in a cooperative approach can play in the learning of school skills and the building of social ties. In particular, it will be necessary to report the feelings of pupils ASD with low verbal and that of neurotypical pupils when they are brought to work in cooperation, through a digital working environment.